Neurobiology of Anorexia Nervosa: Serotonin Dysfunctions Link Self-Starvation with Body Image Disturbances through an Impaired Body Memory - Riva, Giuseppe (Frontiers in Human Neuroscience, 2016)
The etiology of anorexia nervosa (AN) is still unclear, despite that it is a critical and potentially mortal illness. A recent neurobiological model considers AN as the outcome of dysfunctions in the neuronal processes related to appetite and emotionality (Kaye et al., 2009, 2013). However, this model still is not able to answer a critical question: What is behind body image disturbances (BIDs) in AN? The article starts its analysis from reviewing some of the studies exploring the effects of the serotonin systems in memory (episodic, working and spatial) and its dysfunctions. The review suggests that serotonin disturbances may: a) facilitate the encoding of third person (allocentric) episodic memories; b) facilitate the consolidation of emotional episodic memories (e.g. teasing), if preceded by repeated stress; c) reduce voluntary inhibition of mnestic contents; d) impair allocentric spatial memory. If we discuss these results within the interpretative frame suggested by the “Allocentric Lock Hypothesis” (Riva, 2012, 2014), we can hypothesize that altered serotoninergic activity in AN patients: i) improve their ability to store and consolidate negative autobiographical memories, including those of their body, in allocentric perspective; ii) impair their ability to trigger voluntary inhibition of the previously stored negative memory of the body; iii) impair their capacity to retrieve/update allocentric information. Taken together, these points suggest a possible link between serotonin dysfunctions, memory impairments and BIDs: the impossibility of updating a disturbed body memory using real time experiential data – I’m locked to a negative body stored in long term memory - pushes AN patients to control body weight and shape even when underweight.